2018
DOI: 10.1016/j.molcel.2018.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Injury Activates Ca2+/Calmodulin-Dependent Phosphorylation of JAV1-JAZ8-WRKY51 Complex for Jasmonate Biosynthesis

Abstract: Insect herbivory causes severe damage to plants and threatens the world's food production. During evolutionary adaptation, plants have evolved sophisticated mechanisms to rapidly accumulate a key defense hormone, jasmonate (JA), that triggers plant defense against herbivory. However, little is known about how plants initially activate JA biosynthesis at encounter with herbivory. Here, we uncover that a novel JAV1-JAZ8-WRKY51 (JJW) complex controls JA biosynthesis to defend against insect attack. In healthy pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
162
2
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(169 citation statements)
references
References 55 publications
1
162
2
4
Order By: Relevance
“…Some early signaling events triggering specific cellular responses and defense gene activation after wounding bear similarities between plants and animals (Mueller, 1998;Navarro et al, 2008). The cyclopentanoic fatty acid derivatives including the plant defense hormone JA is structurally similar to the animal defense regulators of the prostaglandin family (Creelman and Mullet, 1997;Yan et al, 2018). Both JA and prostaglandin are synthesized quickly in response to localized and/or systemic stress and inflammatory responses in plant or animal cells, respectively (Mueller, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some early signaling events triggering specific cellular responses and defense gene activation after wounding bear similarities between plants and animals (Mueller, 1998;Navarro et al, 2008). The cyclopentanoic fatty acid derivatives including the plant defense hormone JA is structurally similar to the animal defense regulators of the prostaglandin family (Creelman and Mullet, 1997;Yan et al, 2018). Both JA and prostaglandin are synthesized quickly in response to localized and/or systemic stress and inflammatory responses in plant or animal cells, respectively (Mueller, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The stress hormone JA, structurally similar to the animal defense regulator prostaglandin (Mueller, 1998), is a candidate trigger for regeneration responses. JA plays well-established roles in defense responses against necrotrophic pathogens and insect herbivores, and also in abiotic stress responses, reproductive development, and metabolism (Pieterse et al, 2012;Yang et al, 2012;Yan et al, 2018). JA rapidly accumulates after damage and pathogen detection cues (Glauser et al, 2009;Larrieu et al, 2015;Wasternack and Hause, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This notion was introduced earlier for some JAZ genes in single or double mutants of one pathway, but its relevance was difficult to assess in single biological situations investigated in a limited set of genetic backgrounds (Aubert et al, ; Heitz et al, ; Koo et al, ; Widemann et al, ). Here, we surveyed three gene families of characterized transcriptional repressors in the JA pathway in the different pathway/genotype/stress combinations: in addition to several JAZ , we also analyzed expression of JAM , a second type of negative regulator inhibiting transcription of JA‐Ile‐ and MYC‐regulated genes (Liu et al, ; Sasaki‐Sekimoto et al, ), and JAV1 , that directs a calcium‐sensitive complex repressing JA responses (Yan et al, ). We found a robust negative correlation spanning both pathosystems between the behaviour of several JAZ , JAM , and JAV1 genes and the amplitude and timing of defense response under impaired JA‐Ile turnover (summarized in Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…For appropriate control of JA responses, plants rely on several negative feedback mechanisms. In addition to JAZ repressor proteins, other negative regulators were identified that repress JA responses at the level of gene promoters, including JAV1 (Yan et al, ), and the JAM subclass of bHLH proteins that compete with MYC2/3/4 TFs (Sasaki‐Sekimoto et al, ). Another way to repress or terminate jasmonate action is at the metabolic level, either by diverting the flux to hydroxy‐JA rather than to JA‐Ile (Smirnova et al, ) or by modifying JA‐Ile to alleviate its receptor‐binding properties.…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence indicates that VQ proteins interact with WRKY TFs via the conserved V and Q residues, and that the amino acid residues flanking the core VQ motif are also required for the interaction with the WRKY domains and are important regions for the specificity of VQ-WRKY binding [20,37]. Many studies have shown the interactions among various VQ proteins and WRKY TFs to be significantly important for the growth and development of plants, such as the interactions between AtVQ9 and WRKY8 [28], AtVQ14 and MINISEED3/WRKY10 [29], AtVQ20 and WRKY2 and 34 [31], AtVQ21 and WRKY25 and 33 [32,33], AtVQ22 and WRKY28 and 51 [35,66], as well as AtVQ23 and WRKY33 [37]. Although evidence of the interactions between VQ proteins and WRKYs in tobacco is limited, it is of considerable significance to functionally characterize these small proteins in tobacco due to the important roles they are potentially playing during plant growth and development.…”
Section: Expression Analysis Of Ntvq Genes In Response To Biotic and mentioning
confidence: 99%